PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI DI KANTOR KELURAHAN TUALANG KECAMATAN PERBAUNGAN KABUPATEN SERDANG BEDAGAI - Gentri Waruwu; Cindy Putri Maharani Dachi; Cut Sah Kha Mei Zsazsa (Jurnal Genta Mulia, 2024)
The purpose of this research is to determine the effect of work discipline on employee performance at the Tualang Village Office, Perbaungan District, Serdang Bedagai Regency. The research method used is quantitative research. The population in this study were all employees and TP PKK of the Tualang District Office, totaling 45 people who also formed the sample size in this study. The data analysis technique in this research uses the t test, F test, and determination test (R2). The results of this research show that there is a positive and significant influence between work discipline on employee performance with the t test obtaining a t value of 9.132 > ttable 2.017 and a significance value (sig.) of 0.000 < 0.05, as well as a determination test with a coefficient of determination (R2) value is 0.660 or worth 60.0%. Thus it can be concluded that work discipline influences employee performance.